Motivational Interviewing to Improve Inherent and Social Dignities Among Patients Undergoing Hemodialysis - Heydarinezhad, Fatemeh; Bagheri, Hossein; Talebi, Seyedeh Solmaz; Imani, Maryam; Mirhosseini, Seyedmohammad; Khajeh, Mahboobeh (Shahroud Journal of Medical Sciences, 2025)
Background: Motivational interviewing (MI) is a patient-centered counseling approach aimed at enhancing intrinsic motivation for behavior change by addressing ambivalence. While MI has shown promise in improving psychological and social outcomes in chronic illness, its impact on patient dignity remains underexplored. This study evaluated the effect of MI on the inherent and social dignity of hemodialysis patients.Methods: A randomized clinical trial was conducted using convenience sampling with 70 hemodialysis patients in Iran. The intervention group received five 120-minute MI sessions over two weeks, based on Miller and Rollnick’s framework. Participants completed measures of inherent and social dignity before the intervention, immediately afterward, and again four weeks later.Results: At baseline, the two groups were comparable in terms of inherent and social dignity. MI significantly improved both dimensions. Immediately following the intervention, the intervention group had higher total scores in social dignity (P-value=0.015), particularly in the family support and connection dimension (P-value=0.028). Additionally, notable improvements were seen in total inherent dignity (P-value=0.003), as well as in the family environment (P-value=0.001) and social environment (P-value=0.023) subscales.Conclusions: MI significantly enhances both social and inherent dignity among hemodialysis patients, improving their psychosocial well-being. Healthcare managers should consider integrating MI into dialysis care routines to foster patient dignity and overall quality of life. Future studies are recommended to assess the long-term effects of MI and its applicability across broader clinical populations.